First Report of CTX-M-32 and CTX-M-101 in Proteus mirabilis from Zagreb, Croatia - Branka Bedenić; Josefa Luxner; Gernot Zarfel; Andrea Grisold; Mirela Dobrić; Branka Đuras-Cuculić; Mislav Kasalo; Vesna Bratić; Verena Dobretzberger; Ivan Barišić (Antibiotics)
Background/Objectives: Proteus mirabilis is a frequent causative agent of urinary tract and wound infections in community and hospital settings. It develops resistance to expanded-spectrum cephalosporins (ESC) due to the production of extended-spectrum β-lactamases (ESBLs) or plasmid-mediated AmpC β-lactamases (p-AmpC). Here, we report the characteristics of ESBLs and p-AmpC β-lactamases encountered among hospital and community isolates of P. mirabilis in two hospitals and the community settings in Zagreb, Croatia. Methods: Antibiotic susceptibility testing was performed using disk-diffusion and broth dilution methods. The double-disk-synergy test (DDST) and inhibitor-based test with clavulanic and cloxacillin were applied to screen for ESBLs and p-AmpC, respectively. PCR investigated the nature of ESBL, carbapenemases, and fluoroquinolone resistance determinants. Selected strains were subjected to molecular analysis of resistance traits by the Inter-Array CarbaResist Kit and whole-genome sequencing (WGS). Results: In total, 39 isolates were analyzed. Twenty-two isolates phenotypically tested positive for p-AmpC and seventeen for ESBLs. AmpC-producing organisms exhibited uniform resistance to amoxicillin-clavulanate, ESC, ciprofloxacin, and sulphamethoxazole-trimethoprim, and uniform susceptibility to carbapenems and piperacillin-tazobactam and all harbored blaCMY-16 genes. ESBL-positive isolates demonstrated resistance to amoxicillin-clavulanate, cefuroxime, cefotaxime, ceftriaxone, and ciprofloxacin but variable susceptibility to cefepime and aminoglycosides. They possessed blaCTX-M genes that belong to cluster 1 (n = 5) or 9 (n = 12), with CTX-M-14 and CTX-M-65 as the dominant allelic variants. Conclusions: The study demonstrated the presence of CTX-M ESBL and CMY-16 p-AmpC among hospital and community-acquired isolates. AmpC-producing isolates showed uniform resistance patterns, whereas ESBL-positive strains had variable degrees of susceptibility/resistance to non-β-lactam antibiotics, resulting in more diverse susceptibility patterns. The study found an accumulation of various resistance determinants among hospital and outpatient isolates, mandating improvement in detecting β-lactamases during routine laboratory work.